EVALUASI STATUS MUTU AIR SUNGAI TUKAD OOS KABUPATEN GIANYAR - Ardi Putra, I Kadek; Arimbawa, Wahyudi; Wiratama, I Gusti Ngurah Made (Jurnal Ecocentrism, 2025)
This study was conducted to evaluate the water quality status of the Tukad Oos River in Gianyar Regency based on physical, chemical, and biological parameters, namely temperature, pH, DO, BOD, COD, phosphate, nitrate, and coliform. The research was motivated by increasing anthropogenic activities, such as domestic waste disposal, which potentially degrade river water quality. Sampling was carried out at six points representing the upstream, middle, and downstream segments during two observation periods using the grab sampling method. Laboratory analyses were conducted with reference to the Standard Methods for the Examination of Water and Wastewater, while the water quality status was assessed using the Pollution Index (PI) method based on Class II water quality standards according to Government Regulation No. 22 of 2021. The results showed that temperature 24–30°C, TSS <2–8 mg/L, pH 6.5–8, BOD 2.0–2.7 mg/L, and COD 12–24 mg/L were still below the allowable thresholds, and the PI values ranged from 0.623 to 0.770, indicating that all river segments were categorized as “good” or “unpolluted.” However, there was a tendency for increased temperature, COD, and coliform levels in the downstream segment due to domestic and agricultural activities. This indicates the need for future anticipation efforts through routine monitoring and integrated watershed management to prevent further degradation.